Writing Errors in Hospitality Students' Descriptive Paragraphs: A Descriptive Qualitative Study - Dwi Cahyono; Dyah Rohma Wati; Risqi Ekanti Ayuningtyas Palupi (Pustaka Bangsa Indonesia, 2026)
This study aimed to identify and analyze writing errors in descriptive paragraphs produced by hospitality students in an English for Hospitality course. A qualitative case study was conducted involving 23 Diploma III Hospitality students at Universitas Muhammadiyah Karanganyar selected through purposive sampling. Data were collected from students' descriptive writing assignments and analyzed using qualitative content analysis. Errors were classified into grammar, vocabulary, spelling, and punctuation. The findings showed that grammatical errors were the most dominant, particularly in subject verb agreement, article usage, verb forms, and prepositions. Vocabulary errors mainly involved inappropriate lexical choices related to hospitality contexts, while spelling and punctuation errors occurred less frequently. These findings indicate that students still face challenges in producing accurate descriptive writing. Therefore, contextualized writing instruction and continuous feedback are essential to improve students' writing competence and support effective professional communication in the hospitality industry.